Role of the PI3K-Akt Signaling Pathway in the Pathogenesis of Polycystic Ovary Syndrome. (May 2017) - Li, Tiantian; Mo, Hui; Chen, Wenfeng; Li, Li; Xiao, Yao; Zhang, Jing; Li, Xiaofang; Lu, Ying
This review aimed to focus on the recent progress of the understanding of the role of phosphatidylinositol 3-kinase (PI3K) in polycystic ovary syndrome (PCOS). In recent years, it has been increasingly recognized that PI3K plays an important role in PCOS whose pathogenesis is unclear. However, research continues into revealing the details of how PI3Ks are involved in developing PCOS. Previous studies have shown that activation of the PI3K-protein kinase B (Akt) signaling pathway has important effects on insulin resistance and endometrial cancer. Knowledge of the action of PI3K in PCOS might provide valuable information to further validate the pathogenesis of PCOS and suggest new methods of treatment.